Influencing Consumers’ Satisfaction To Organic Timor Coffee Products - E.S. Nunes, Aderito; Suwasono, Son; Rusdiana, Endang; DJ. Gomes, Julio (Jurnal Syntax Fusion, 2024)
Consumers’ satisfaction were determined by the quality of expected products. There wher, quality warrantly that becomes the priority of every company, especially nowadays it becomes the basic measurement of competiveness superiority of every company. Gerson (2002) defines that consumers’ satisfaction is a consumers’ perception that their expectaion has been come true. According to Dutka (1994) there are several main factors affecting consumers’ satisfaction to a product, they are: price, quality, benefit, package, reliability of the product, and service offered by the company. This study aimed to determine the effects of simultaneously, partially, and dominantly of price, quality, benefit, and package factor affecting consumers’ satisfaction of Timor Organic Coffee. This study used 105 respondents of Timor Organic Coffee consumers. The data analysis used multiple linear regression. The results show that price, quality, benefit, and package factor simultanously affect significantly to consumers satisfaction of Timor Organic Coffee. The linear regression equation formed is: Y = - 1.975 + 0.190 X1 + 0.095 X2 + 0.415X3 + 0.462X4 + e ( R square = 0,914) the value of determination coefficient (R square) = 0.914 meaning that independent variable can explain consumers’ satisfaction as many as 91.4%, whereas the revenue is other variables which are not included in this study. Price, benefit, and package factor partially affect positively and significantly to consumers’ satisfaction, and quality factor partially does not affect significantly to consumers’ satisfaction. Based on regression coefficient, it is got that package variable has a high value so that package factor becomes the dominant factor affecting consumers’ satisfaction of Timor Organic Coffee.